Audiometric Outcomes in Pediatric Temporal Bone Trauma. (6th October 2015) - Schell, Amy; Kitsko, Dennis
Abstract : Objective: To characterize pediatric temporal bone trauma, focusing on audiometric outcomes. Study Design: Case series with chart review. Setting: Tertiary care children's hospital. Subjects and Methods: Cases were reviewed of children (<18 years) presenting over a 3‐year period with computed tomography–proven temporal bone fracture and audiology examination. All scans were read by a neuroradiologist and reviewed by a pediatric otolaryngologist. Demographics, fracture pattern, and audiometric data were recorded. Results: Fifty‐eight patients (60 fractures) met inclusion criteria. The majority (93%) were otic capsule–sparing fractures. The types and severity of hearing loss were significantly different between the 2 fracture patterns. Based on pure‐tone average, all otic capsule–violating fractures had abnormal initial audiograms; 75% of these losses were severe. Approximately half (54%) of otic capsule–sparing fractures had abnormal initial audiograms; a majority were mild losses (85%). All classifiable losses in otic capsule–violating cases were of mixed type, whereas the majority (75%) of losses in otic capsule–sparing cases were conductive. Regardless of classification, 72% of patients with otic capsule–sparing fractures and initially abnormal audiograms improved to normal levels at a mean of 48 days posttrauma; this increased to 83% when only conductive losses were considered. Conclusions: Hearing loss type and severity differ in otic capsule–sparing and otic capsule–violating temporal bone fractures. A majority of children with otic capsule–sparing fractures and associated hearing loss improve to normal levels in about 6 weeks, especially if the original loss is classified as solely conductive. Children who do not improve within this time frame may warrant early investigation into surgically correctable causes.